Arap toplumunda cinsiyetlerin oluşumunda çocuk yetiştirme pratiklerinin rolü - Babahan, Ali (My University, 2005)
This study examins the role of child rearing practices, as one of the means of the construction of genders, in the formation of genders and the gender system of Arab society. Various works, primarily, show that parenting is gendered in all societies around the world. In other words, all parents in every society behave differently to their children considering their sexes. Within the patriarchal system, especially related with economical reasons, the parent's view is that boys have more reputation than daughters do. However, new researches reveal that parents are behaving with less discrimination in developed societies. The most important reason of this change is the decrease of importance of gender differences in the present economic and production oriented conditions of Western societies. When Arab society is examined, contrary to developed societies, it is seemed that traditional patriarchal system and gendered childrearing practices are still binding. Despite the heterogenity of the population, this tendency is common among different Arab collecitivities. The main reasons for this condition is fundamentally the lack of developed economy and industrial production, and also the conservative interpretation of Qur'an throughout the Arab world. In this way, the gendered childrearing practices begin as soon as the baby is born and continues until the child is married. During this period, parents behave dissimilar to their sons and daughters, and pamper boys more than girls. The gender discriminating behaviour of parents bring forth self-relying, authoritarian, dominant, chivalrous and audiacious boys and obedient, hard working, fastidious, devoted and silent girls, hence allow continuation of the formation of genders as social categories
Keywords: Cinsiyet; Çocuk Gelişimi, Sosyolojide; Genç insanlar; Sosyal guruplar; Toplum bilimleri; Yaş gurupları